PERFORMANCE OF QUAIL BIRD AGED 4-8 WEEKS WHICH IS GIVEN TURMERIC SOLUTION ON DRINKING WATER - I. B. M. G., Sukmaya; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 9 No 3 (2021): Vol. 9 No. 3 Tahun 2021; September - December, 2021)
This study aims to determine the effect of giving turmeric solution in drinking water on the performance of quail aged 4-8 weeks. The research design used was a completely randomized design (CRD) with 3 treatments and 6 replications each replications consisting of 3 quails. The treatments consisted of drinking water without turmeric solution (A); drinking water with 1% turmeric solution (B); and drinking water with 2% turmeric solution (C). The variables observed were initial body weight, final body weight, ration consumption, drinking water consumption, weight gain and feed conversion ratio (FCR). The results showed that administration of 2% turmeric solution in drinking water (C) had an significant effect on feed conversion ratio (FCR) from the control treatment but had no significant effect (P>0,05) on final body weight, ration consumption, drinking water consumption and increase in body weight compared to A (without turmeric solution in drinking water) and B (1% turmeric solution in drinking water). Based on the results of the study, it was concluded that the quail aged 4-8 weeks gave of a 2% turmeric solution had a significant effect on the feed conversion ratio (FCR) of the control treatment, but between the control treatments, 1% and 2% turmeric solution on water whit no significant effect ration consumption, drinking water consumption, final body weight, and weight gain body.   Key word s : turmeric, quail, performance.